Three-Dimensional Osteosynthesis Plates for the Surgical Treatment of Mandibular Fractures. Issue 8 (November 2021) - Khalil, Sherin; Khamis, Hamza; Kauke, Martin; Iizuka, Tateyuki; Safi, Ali-Farid
Abstract : Objectives: Mandible fractures can be treated with different plate systems, that is, miniplates or three-dimensional (3D) plates. This systematic review describes the effectiveness and clinical outcomes of 3D plates used in fractures of the mandible and aims to critically evaluate its risks and benefits. Materials and Methods: A comprehensive electronic search was conducted without date but with restriction to articles written in English. Studies in humans, including randomized or quasi-randomized controlled trials and retrospective studies, were included. The outcome parameters measured were number of patients, fracture classification, results, follow-up period, postoperative complications, and mean age of patients. Major complications were defined as those needing additional surgical intervention, for example, malocclusion, infection or plate fracture. Accordingly, complications not needing additional surgical intervention were defined as minor (ie, dehiscence, trismus). Results: Guided by the PRISMA statement and the Cochrane Handbook for Systematic Reviews of Interventions, the authors identified 44 publications with a total of 1790 patients. Among the articles selected for the final review, there were 32 reported prospective studies, 12 reported retrospective studies. Regarding the evaluation of quality, 8 studies showed a low value of the risk of bias, 17 a moderate risk, and 19 a high risk. There were statistically significant advantages for 3D plates in mandibular fractures in terms of postoperative complications, for example, wound dehiscences or plate fracture. Conclusions: The 3D plate is an effective treatment modality for mandibular fractures, with low incidence of major complications, decreased length of operation time, and increased stability of osteosynthesis. Abstract : Supplemental Digital Content is available in the text